IMPLIKASI ASEAN ECONOMIC COMMUNITY (AEC) TERHADAP PENGGUNAAN TENAGA KERJA ASING DI KARIMUN - Tasya Syahfitri; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research aims to discuss the implications of the ASEAN Economic Community (AEC) on the use of foreign workers in Karimun Regency. The purpose of this study is to identify and explain the impact of the realization of the ASEAN Economic Community on the use of foreign workers in Karimun. AEC which is the background for the incidence of free trade in the use of foreign workers in Karimun. So, that in its use there is an increase and decrease in the number of foreign workers in Karimun, with some things that are the factor in these issues. This research is a qualitative research, which is done by explaining the case based on facts with a level of group behavior analysis. The author uses the interdependence theory in the concept of regionalism by using the perspective of neoliberalism. To discuss this issue, the authors collected data from books, journals, websites, an official document, and data reports from Dinas Ketenagakerjaan, Tanjung Balai Karimun Class II Immigration Office and TIMPORA Karimun Regency, in the implications of the ASEAN Economic Community (AEC) on the use of labor foreigners in Karimun. The result of this research shows that the use of foreign workers in Karimun is fluctuating, such as the increase occurred because Karimun is a border area and free trade, an increase in foreign workers as many as 3,300 peoples after the realization of the AEC in early 2016, the existence of demand and opportunities to use labor foreigners in the industrial sector and the decline occurred due to foreign companies moving operations to areas affected by the existence of AEC, the role of the government in tightening the supervision of foreign workers who entered illegally. Therefore, the implications of AEC on the use of foreign workers in Karimun are not too significant but have an impact on the number of their use.  Keywords: Implications, ASEAN Economic Community, Foreign workers, Karimun, Interdependence theory.